(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2003)
The article gives a brief review of principles of archaeomagnetic dating method. Presented curves of secular variations of geomagnetic field parameters in a historical period of time for the territory of Armenia, obtained on the hypothesis dipole of Earth’s magnetic field. A new method of sample splitting from ovens and hearths is presented. Archaeomagnetic dating of archaeological sites of Armenia is done.